RUMINNAT NUTRITION SYMPOSIUM: Tiny but mighty: the role of the rumen microbes in livestock production. (27th January 2018) - Cammack, Kristi M; Austin, Kathleen J; Lamberson, William R; Conant, Gavin C; Cunningham, Hannah C
Abstract: The microbes inhabiting the rumen convert low-quality, fibrous, plant material into useable energy for the host ruminant. Consisting of bacteria, protozoa, fungi, archaea, and viruses, the rumen microbiome composes a sophisticated network of symbiosis essential to maintenance, immune function, and overall production efficiency of the host ruminant. Robert Hungate laid the foundation for rumen microbiome research. This area of research has expanded immensely with advances in methodology and technology that have not only improved the ability to describe microbes in taxonomic and density terms but also characterize populations of microbes, their functions, and their interactions with each other and the host. The interplay between the rumen microbiome and the host contributes to variation in many phenotypic traits expressed by the host animal. A better understanding of how the rumen microbiome influences host health and performance may lead to novel strategies and treatments for trait improvement. Furthermore, elucidation of maternal, genetic, and environmental factors that influence rumen microbiome establishment and development may provide novel insights into possible mechanisms for manipulating the rumen microbial composition to enhance long-term host health and performance. The potential for these tiny but mighty rumen microbes to play a role in improving livestock production is appreciated despite being relatively obscure.